Rekonsiliasi Nilai Demokrasi dan Birokrasi dalam Proses Formulasi Kebijakan Publik - Maria Rosarie Harni Triastuti (Jurnal Administrasi Publik, 2003)
The process of Public Policy Formulation is filled with paradoxical relations between democracy and bureaucracy. This paper starts by illustrating the paradoxical relations between democratic values and bureaucratic values. Then the author suggests a mechanism for reconciliation between these two values. The first precondition for the success of the mechanism is the positioning of the relationship between government and society in the formulation of public policy. The government role should be changed into its previous role as agent, while the role of the society should replace the government as the principle. The second precondition is the dialogical democratic atmosphere which is the dialogical process between policy maker and policy stakeholder. Conceptual reconciliation will succeed if the bureaucracy and society are mature and independent. Furthermore empirically reconciliation must be supported by reciprocal and equal communication between public administrations and the public, mechanisms for checks and balances, strong civil society and responsive and dynamic beureaucracy. Pluralism is important in Public Policy Study. When democracy is strongly incorporated into public policy formulation, pluralism could potentially cause conflict or form the basis for democratic processes. The next important issues are social justice and gender justice. Both are important, especially in public policy study which is developed in the framework of democratization with the values of freedom, egalitarianism and justice.